New, previously unreported correlations between latent Toxoplasma gondii infection and excessive ethanol consumption. (November 2017) - Samojłowicz, Dorota; Borowska-Solonynko, Aleksandra; Kruczyk, Marcin
Highlights: Prevalence of toxoplasmosis in the victims of risky behaviour was increased. The probability of a positive blood alcohol test was higher in Toxoplasma gondii -infected risk-takers. This positive association was the highest in victims of suicides and poisoning. This association was nonsignificant (and negative) in drivers. Abstract: A number of world literature reports indicate that a latent Toxoplasma gondii infection leads to development of central nervous system disorders, which in turn may lead to altered behavior in the affected individuals. T. gondii infection has been observed to play the greatest role in drivers, suicides, and psychiatric patients. Studies conducted for this manuscript involve a different, never before really reported correlation between latent T. gondii infection and ethanol abuse. A total of 538 decedents with a known cause of death were included in the study. These individuals were divided into three groups: the risky behavior group, inconclusively risky behavior group, and control group. The criterion for this division was the likely effect of the individual's behavior on the mechanism and cause of his/her death. The material used for analyses were blood samples collected during routine medico-legal examinations in these cases. The blood samples were used to measure anti- T. gondii IgG antibodies with an enzyme-linked immunosorbent assay (ELISA). Moreover, the following data were recorded for each decedent: sex, age, circumstances of death, cause of death, time from death to autopsy, and (if provided) substance abuse status (alcohol, illicit drugs). In those cases where blood alcohol level or toxicology tests were requested by the Prosecutor's Office, their results were also included in our analysis. Test results demonstrated a strong correlation between latent T. gondii infection and engaging in risky behaviors leading to death. Moreover, analyses demonstrated a positive correlation between the presence of anti- T. gondii IgG antibodies and psychoactive substance (especially ethanol) abuse, however, the causal relationship remains unclear. Due to the fact that alcohol abuse constitutes a significant social problem, searching for eliminable risk factors for addiction is extremely important. Our analyses provided new important information on the possible effects of latent T. gondii infection in humans.